THE EFFECT OF LEVERAGE, INSTITUTIONAL OWNERSHIP, AND BUSINESS STRATEGY ON TAX AVOIDANCE (CASE OF LISTED MANUFACTURING COMPANIES IN THE CONSUMPTION GOODS INDUSTRY PERIOD 2014-2019) - Damayanti, Vina Novia; Wulandari, Sartika (ACCOUNTABILITY, 2021)
This study aims to obtain empirical evidence regarding the influence of leverage, institutional ownership, and business strategy on tax avoidance of consumer goods industrial sector manufacturing companies listed in Indonesia Stock Exchange (IDX) under period 2014-2019. The results show that leverage and goods production and distribution have a significant positive effect on tax avoidance while institutional ownership and firm growth have a negative significant effect on tax avoidance. The findings imply that in the context of agency theory, firms shall use debts for tax avoidance in term to reduce the tax but the institutional ownerships tend to control the firm to avoid the tax avoidance.